Exploring the differential effects of career and psychosocial mentoring on newcomer socialization - Deng, Hui; Wu, Wenbing; Zhang, Yihua; Yu, Zhuyan; Xu, Hanzhi; Wu, Wen (Frontiers in Psychology, 2022)
Drawing upon social cognitive career theory, this study proposed an integrative framework to uncover how and when different types of mentoring accelerate newcomers socialized in corresponding domains. We tested this relational model with time-lagged, multisource survey data collected from 157 newcomers and 88 supervisors. In particular, the results indicated that career mentoring facilitated newcomer task mastery, task performance, and job satisfaction through improving newcomer occupational self-efficacy, whereas psychosocial mentoring promoted newcomer job satisfaction and social integration via inspiring newcomer social self-efficacy. Further, newcomer learning adaptability amplified the influence of career mentoring on newcomer occupational self-efficacy, as well as the impact of psychosocial mentoring on newcomer social self-efficacy. Our study extended the mentoring and socialization literature by revealing the differential influences of career and psychosocial mentoring in facilitating newcomer task-related and social outcomes, and provided significant practical implications for managers on how to arrange tailored mentoring to facilitate newcomer socialization.